Types of Political Metaphors in the Indonesian Mass Media - Surip, M.; Lubis, M. Joharis (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2022)
The purpose of the study was to reveal political metaphor data focused on classifying types of conceptual metaphors. The data source used is the text of political discourse in the Indonesian national mass media (kompas, antaranews, republika, detik, and waspada). Research data in the form of lingual units, both lexical and grammatical in the form of metaphors. The data collection method is used by the concept of metaphor identification procesure, while the data processing method is carried out based on conceptual metaphor analysis through three classifications, namely structural, ontological and orientational metaphors. The data analysis method uses referential methods, to show and compare references or meanings contained in the realm of source and target metaphorical speech. The study found that the types of conceptual metaphors in political discourse are identical through attempts at concretizing abstract concepts. The expression of political metaphor is a form of simplification of concepts that are correlated with human sensory experience. Ontological metaphors give a living perception of inanimate objects, both concrete and abstract. Ontological metaphors also allow units of language to present space to be filled and juxtaposed with other concepts because they have similar substances. While orientational metaphors tend to point to parts of the human body through the association of political terminology and cultural realities in society.